PERSPEKTIF EKONOMI POLITIK PENGEMBANGAN PARIWISATA CANDI PRAMBANAN - Sambung Widodo (BRIN, 2006)
It is very interesting to observe the journey of Prambanan Temple as a cultural heritage, which was initially managed as a hobby and a love for monumental works of art, until now as a world cultural heritage that is used as a product / attraction of the tourism industry. It is interesting because the journey illustrates the dynamics that reflect the complexity of tourism problems, both regarding social, cultural, economic and ecological aspects.